Los medios de comunicación en las decisiones migratorias de ecuatorianos hacia Estados Unidos: Un análisis de contenido y percepciones públicas - Llanos Marmolejo Ariana Lilibeth (2024)
This research focuses on analyzing the impact of the media on the migratory decisions of Ecuadorians towards the United States, with an emphasis on the content and public perception in Ecuadorian media. The main objective is to examine how media coverage influences the migration decisions of the population, using a methodology that integrates documentary and descriptive research. The study was conducted in the Ciudadela El Chorrillo, located in Babahoyo, where a representative sample of 508 inhabitants was selected. Techniques such as bibliographic collection and surveys were employed to obtain both quantitative and qualitative data. Methods like observation and content analysis were used to gain a deeper understanding of the social context and the factors affecting migratory decisions. The results indicate that there is a poor relationship between the media and the population, marked by a lack of specific and accurate information about migration. Most inhabitants, primarily young people, lack detailed knowledge about the reality of migrants, which negatively impacts their decisions and the formation of opinions on the migratory phenomenon. Although many consult various information sources, the information provided by the media does not meet their informational needs, leading to confusion and distrust. Additionally, it was found that, while inhabitants mainly use digital media for information, this information is often unclear or incomplete. Social media and other online platforms, while allowing for immediate access to information, do not guarantee the quality or accuracy of the content, which directly influences their perceptions of migration. In conclusion, the research emphasizes the importance of improving the quality of information provided by the media in order to positively influence the migratory decisions of Ecuadorians. It is recommended that media outlets commit to accuracy and clarity in their coverage, as well as take greater responsibility in shaping public opinion on this highly relevant issue for Ecuadorian society.